Bilateral Advantages in Subitizing With Visual Masking. (June 2015) - Pryor, Campbell G.; Howe, Piers D. L.
Performance on a range of visual-processing tasks has been shown to improve when information is split bilaterally across the left and right visual hemifields rather than being restricted to a single visual hemifield. However, a recent study by Delvenne et al. found no such bilateral advantage for subitizing, which is our ability to rapidly and accurately enumerate small quantities of objects. This finding is particularly surprising, as it contradicts the prediction of FINgers of INSTantiation theory that subitizing should benefit from bilateral presentation. Our study investigated the issue by determining if there are any circumstances where a bilateral advantage for subitization occurs. Contrary to Delvenne et al., we found that subitizing could show bilateral advantages, but only when the display was backward-masked. We discuss these findings in relation to how the rate of encoding and the time available for this encoding may affect bilateral advantages in subitizing. A general model is proposed under which bilateral advantages could be explained.